2017
DOI: 10.1111/cdev.12902
|View full text |Cite
|
Sign up to set email alerts
|

Does Temperament Underlie Infant Novel Food Responses?: Continuity of Approach–Withdrawal From 6 to 18 Months

Abstract: This study investigated whether temperamental approach-withdrawal underlies infants' responses to novel foods. Data were drawn from a longitudinal study of mother-infant dyads (n = 136). Approach-withdrawal responses to novel foods and novel toys were coded when infants were 6 and 12 months of age. When infants were 18 months of age, approach-withdrawal behaviors, positive affect, and negative affect were used in a latent profile analysis to identify groups of toddlers who exhibited similar responses to novelt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…These findings are consistent with those of Mennella and colleagues (2017) who reported that young infants (∼8 mo of age) readily accepted a novel carrot-flavored cereal after exposure to carrot flavor through their mother's breastmilk ( 23 ). They concluded that the early period of complementary feeding “may be an optimum time for [the] infant … to learn to like the taste of healthy foods.” Our findings, though from a cross-sectional study design, align with those of Mennella and others ( 23 , 26 , 27 , 56 ) and together indicate that introduction to new foods in general, and in our study, a bitter green vegetable, may be more easily achieved early on in the complementary feeding process. More research could help to determine whether critical periods exist for development of food acceptance patterns and whether early acceptance is associated with later intake ( 3 ).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with those of Mennella and colleagues (2017) who reported that young infants (∼8 mo of age) readily accepted a novel carrot-flavored cereal after exposure to carrot flavor through their mother's breastmilk ( 23 ). They concluded that the early period of complementary feeding “may be an optimum time for [the] infant … to learn to like the taste of healthy foods.” Our findings, though from a cross-sectional study design, align with those of Mennella and others ( 23 , 26 , 27 , 56 ) and together indicate that introduction to new foods in general, and in our study, a bitter green vegetable, may be more easily achieved early on in the complementary feeding process. More research could help to determine whether critical periods exist for development of food acceptance patterns and whether early acceptance is associated with later intake ( 3 ).…”
Section: Discussionsupporting
confidence: 92%
“…Surgency is a cluster of temperament characteristics (e.g., high activity level, high intensity pleasure, approach behaviors) that indicate an approach orientation to new objects, people, and situations. Recently, Moding & Stifter ( 37 ) showed that greater approach to novelty in infancy and toddlerhood to be to be related to positive responses to new foods. This underlying approach motivation may explain past findings linking greater negativity to higher weight status.…”
Section: Discussionmentioning
confidence: 99%
“…However, precursors of food neophobia might be present in infancy. In a series of longitudinal studies, Moding and Stifter (2016a, 2016b, 2018) found that infants who exhibited low approach tendencies toward new foods and high levels of food refusals at 12 months of age had high levels of food neophobia at 4 years of age. The authors argued that food neophobia should emerge after infants’ transition to solid foods (and therefore novel foods), only after the first half of the first year of life.…”
Section: Precursors Of Food Neophobia In Infancymentioning
confidence: 99%